2014
DOI: 10.1371/journal.pone.0085407
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Habitat Origin Influence Biomass Production and Storage Translocation in the Clonal Plant Aegopodium podagraria

Abstract: Through physiological integration, clonal plants can support ramets in unfavourable patches, exploit heterogeneously distributed resources and distribute resources that are taken up over large areas. Physiological integration generally increases in adverse conditions, but it is not well known which factors determine the evolution of physiological integration. The aim of this study was to investigate if clonal plants from Southern and Northern populations of the clonal herb Aegopodium podagraria differed in phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…It has been repeatedly demonstrated that aboveground biomass is positively correlated with flowering intensity and seed production (e.g., [ 43 48 ]). In addition, the studied species not only reproduce generatively but also show extensive vegetative reproduction [ 23 ], and the intensity of clonal reproduction is also a function of plant size ([ 49 ], [ 50 ]). Plant aboveground biomass is thus expected to be a suitable proxy for plant fitness in these species.…”
Section: Methodsmentioning
confidence: 99%
“…It has been repeatedly demonstrated that aboveground biomass is positively correlated with flowering intensity and seed production (e.g., [ 43 48 ]). In addition, the studied species not only reproduce generatively but also show extensive vegetative reproduction [ 23 ], and the intensity of clonal reproduction is also a function of plant size ([ 49 ], [ 50 ]). Plant aboveground biomass is thus expected to be a suitable proxy for plant fitness in these species.…”
Section: Methodsmentioning
confidence: 99%
“…5). Numerous studies have shown that reduction of soil nutrients will significantly increase the allocation of root biomass to capture more resources (Watson 1984, Jónsdóttir and Watson 1997, Wang et al 2009, Song et al 2013, D'Hertefeldt et al 2014. In our experiment, the amount of N remained constant but P decreased gradually.…”
Section: Discussionmentioning
confidence: 43%
“…We did not find high costs of maintaining stolon connection in CS 7:1 compared to high N/P availability, indicating that low N/P ratio easily compensate for resource investment into the stolon connection of Z. japonica in homogeneous environments. This is the consequence of high resource availability by providing copious resources for plant growth and reproduction, and thus the costs of plants on a certain trait (physiological integration) can be considerably aggravated by high N/P nutrient supply (D'Hertefeldt andJónsdóttir 1999, D'Hertefeldt andFalkengren-Grerup 2002). With respect to the different main parts of Z. japonica, the present study provide evidence regarding plant response and tolerance to clipping.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations